Peran pendidikan akuntansi forensik dan pancasila dalam pencegahan kecurangan pada generasi muda - Suciyati, Nofita - (Maliki Interdisciplinary Journal, 2026)
The increasing incidence of fraud across various sectors highlights the importance of early preventive efforts through education grounded in ethical and moral values. This study aims to analyze the role of forensic accounting education and Pancasila values in preventing fraudulent behavior among the younger generation. The research employs a qualitative approach using a literature review of relevant scientific journals, books, and regulations. The findings indicate that forensic accounting education plays a significant role in enhancing young people’s understanding of the forms, impacts, and consequences of fraud, while Pancasila values, particularly honesty, responsibility, and social justice, serve as a moral foundation in shaping character and ethical attitudes. The integration of forensic accounting education with the reinforcement of Pancasila values has the potential to foster ethical awareness and integrity, thereby serving as a preventive measure to reduce the potential for fraud in the future.